Development of Picture Story Books Based on Sasak Local Wisdom For Grade V Students at SDN 2 Sakra - Suhaemi; Sukri; Irawan Zain, Moh. (LITPAM, 2025)
Indonesian language learning in elementary schools requires attractive and contextual learning media to increase students' learning interest. This research aims to develop learning media in the form of picture story books based on Sasak local wisdom that are feasible and practical to use for grade V students at SDN 2 Sakra. The research method used is Research and Development (R&D) using the ADDIE development model. This research was conducted at SDN 2 Sakra with grade V students as research subjects. Research instruments included media and material expert validation sheets, teacher response questionnaires, and student response questionnaires. Data were analyzed descriptively qualitatively and quantitatively by calculating feasibility and practicality percentages. The novelty of this research is the use of two languages in story presentation, namely Indonesian and Sasak regional language. The research results show that the picture story book based on Sasak local wisdom obtained validation from media experts of 95.78% with very feasible category, material expert validation of 94.67% with very feasible category, teacher response of 96.62% with very practical category, small-scale student response of 90.95% with very practical category, and large-scale student response of 86.94% with very practical category. Based on these results, it can be concluded that picture story books based on Sasak local wisdom are very feasible and practical to use as Indonesian language learning media for elementary school grade V students.